Legislative background and system of China’s Personal Information Protection Law - Xiaoyang YU; Bo HE (大数据)
The Personal Information Protection Law was deliberated in August, 2021 and officially implemented in November, promoting the establishment of China’s legal system for the protection of personal information.Firstly, the background of the Law was systematically introduced, which has gone through three deliberations and adheres to problem orientation, with distinctive features and great significance.Secondly, the rules of the Law were analyzed, focusing on the scope of the concept of personal information, the basic principles of processing personal information, the basis of legality, the rights and obligations of relevant subjects, the cross-border provision rules, as well as the legal liability.Finally, the development of personal information from indirect protection to direct protection and to comprehensive protection was summarized.